The Ethiopia healthcare quality initiative: design and initial lessons learned. (13th December 2019) - Magge, Hema; Kiflie, Abiyou; Nimako, Kojo; Brooks, Kathryn; Sodzi-Tettey, Sodzi; Mobisson-Etuk, Nneka; Mulissa, Zewdie; Bitewulign, Befikadu; Abate, Mehiret; Biadgo, Abera; Alemu, Haregweni; Seman, Yakob; et al.
Abstract: Objective: To describe the development, implementation and initial outcomes of a national quality improvement (QI) intervention in Ethiopia. Design: Retrospective descriptive study of initial prototype phase implementation outcomes. Setting: All public facilities in one selected prototype district in each of four agrarian regions. Participants: Facility QI teams composed of managers, healthcare workers and health extension workers. Interventions: The Ethiopian Federal Ministry of Health (FMoH) and the Institute for Healthcare Improvement co-designed a three-pronged approach to accelerate health system improvement nationally, which included developing a national healthcare quality strategy (NHQS); building QI capability at all health system levels and introducing scalable district MNH QI collaboratives across four regions, involving healthcare providers and managers. Outcome measures: Implementation outcomes including fidelity, acceptability, adoption and program effectiveness. Results: The NHQS was launched in 2016 and governance structures were established at the federal, regional and sub-regional levels to oversee implementation. A total of 212 federal, regional and woreda managers have been trained in context-specific QI methods, and a national FMoH-owned in-service curriculum has been developed. Four prototype improvement collaboratives have been completed with high fidelity and acceptability. About 102 MNH change ideas were tested and a change package was developed with 83 successfully tested ideas. Conclusion: The initial successes observed are attributable to the FMoH's commitment in implementing the initiative, the active engagement of all stakeholders and the district-wide approach utilized. Challenges included weak data systems and security concerns. The second phase—in 26 district-level collaboratives—is now underway.